Effect of Iron Oxide Nanopartical on The FSH, LH and Testesteron Hormones in The offspring of Albino Rats - Reyim Hameid Kamel 1, Amel Ali AL-Taee2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study was carried out to investigate the effect of iron oxide nanoparticle(NP) on FSH,LH and Testosterone hormones in the offspring of albino rats. The study included twenty (20) offspring divided into two groups ,treated and control group . The results of the hormonal study showed the existence of significant increase (P? 0.05) in the mean levels of FSH,LH ,Testosterone of offspring treated groups compared with controls .